Massive paraesophageal hiatus hernia containing colon and stomach with organo-axial volvulus in a child - Şenocak, Mehmet Emin; Büyükpamukçu, Nebil; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 1990)
Paraesophageal hiatus hernia is a very rare entity in children. The majority of cases remain asymptomatic and some are diagnosed incidentally. The clinical course of a massive paraesophageal hiatus hernia containing colon and stomach in a five-year-old boy is presented.
Keywords: paraesophageal hiatus hernia; gastric volvulus; hiatus hernia